Resilience, perception of parental support and socio-educational intervention strategies - Cantarinha, Diana (2016)
Introduction: Resilience is a core variable in the context of studies on the psychosocial adjustment and school children and teenagers, and should be considered in the context of strategies to promote their well- being and quality of life. Objectives: To know the relationship between resilience, parental support and some sociodemographic variables; outline socio-educational intervention strategies in contexts of children’s lives. Methods: This is a non-experimental, correlational and cross-sectional study, having used a non- probabilistic convenience sample consisting of 150 children, aged between 10 and 16 years old, attending the 2nd and 3rd cycles of Basic Education. The gathering instruments were the Sociodemographic Questionnaire, Inventory Measuring State and Child Resilience (Martins, 2005) and Perception Parental Support Scale (Veiga, 2011). Results: Results show that there are signiicant differences in the values of the current, past and overall resilience, between the age groups children, revealing that children aged between 10 and 11 years have higher results in resilience than young people aged between 14 and 16 years. We also observed signiicant differences in the current resilience, depending on the parents’ marital status (higher when parents are married). We also observed positive and signiicant correlations between resilience and perception of parental support. Conclusions: Results are in line with the scientiic literature in the ield that highlights the key role of resilience in school and psychosocial adjustment of children, and should be considered within the design of socio-educational intervention strategies. Keywords: Resilience. Parental support. Attachment